IMPROVING THE ENVIRONMENTAL EFFICIENCY OF THE RETAINING PROCESSOF A LEATHER SEMI-FINISHED PRODUCT - OKHMAT, OLENA; DANYLKOVYCH, АNATOLII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The study aims to improve the environmental efficiency of the tanning stage in the production of elastic leather using alkyl carboxyethanolamines. To investigate the interaction of derma collagen with basic chromium sulfate in the presence of alkylcarboxyethanolamines (ACEA), a double semi-finished product with a thickness of 2.4–2.8 mm after liming was used. The chromium-tanned semi-finished product was further tanned on the initial semi-finished product (heavy beef) after doubling to a thickness of 1.2–1.4 mm, also in the presence of ACEA reagents.The paper investigates the colloidal and chemical properties of the tanning technology for a chrome-tanned semi-finished product using ACEA to obtain an elastic leather material. The surface activity of aqueous solutions of ACEA was determined. In this case, fatty acid surfactants exhibited higher molecular activity compared to naphthenic acid surfactants. The plasticizing effect of the methyl butyl acrylate composition, which includes ACEAs, was found to be similar to the effect obtained in determining the surface tension of their aqueous solutions. The concentration effect of ACEA on the interaction of chromium compounds with derma collagen was also investigated. Effective interaction of chromium compounds with derma collagen in the presence of ACEA was established. The optimal molar ratios of ACEA/Cr2O3 for naphthenic and fatty acids were found to be 0.5–0.6/1.0 and 1.0–1.2/1.0, respectively. At the same time, a high degree of absorption of chromium compounds by derma collagen was achieved for ACEA of fatty and naphthenic acids, reaching 94.0% and 92.0% Cr2O3, respectively, with a more uniform distribution of chromium compounds in the volume of the semi-finished product when using ACEA of naphthenic acids, with a uniformity coefficient of 0.92. The developed ACEA technology for the additional tanning of chrome-tanned semi-finished products ensures the production of a semi-finished product with higher hydrothermal resistance by 7–8°C compared to industrial tanning technology. At the same time, the consumption of chromium compounds is reduced by 40%, and their residue in the waste solution is reduced by 3.7–4.6 times. The resulting semi-finished product meets the requirements of the international standard ISO 5433:2022, and the developed technology for the additional tanning of chrome-tanned semi-finished products can be considered environmentally friendly. The implementation of the developed technology does not necessitate the re-equipping of the leather enterprise with additional equipment. For the practical implementation of the retanning process in industrial conditions, the use of a suspended drum made of stainless steel or polypropylene is recommended.
Keywords: chrome-tanned semi-finished product; retanning; alkylcarboxyethanolamines; chromium compound consumption; physical and chemical properties; equipment of the enterprise